2020
DOI: 10.1002/ctm2.20
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for predicting specific distant metastatic sites and overall survival of colorectal cancer patients: A large population‐based real‐world study

Abstract: Background This study aims to develop functional nomograms to predict specific distant metastatic sites and overall survival (OS) of colorectal cancer (CRC) patients. Methods CRC case data were retrospectively recruited from a large population‐based public dataset. Nomograms were developed to predict the probabilities of specific distant metastatic sites and OS of CRC patients. The performance of nomogram was evaluated with the concordance index (C‐index), calibration curves, area under the curve (AUC), and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…Overall, 541,244 CRC cases were included, involving 1547 patients diagnosed with BM [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The overall average incidence of BM in CRC patients was 2.10% (95%CI 0.98–3.22) ranging from 0.1% up to 11.5% [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Fifty-seven percent of patients were male and 43% were female ( Figure 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 541,244 CRC cases were included, involving 1547 patients diagnosed with BM [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The overall average incidence of BM in CRC patients was 2.10% (95%CI 0.98–3.22) ranging from 0.1% up to 11.5% [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Fifty-seven percent of patients were male and 43% were female ( Figure 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides LM, bone metastases in particular were described as a risk factor [ 8 , 47 , 52 , 53 ]. Mo et al and Yang X.-H. et al identified a positive carcinoembryonic antigen (CEA) level as a risk factor for developing BM [ 7 , 13 ]. The primary CRC side might also have an association with an increased risk of developing BM.…”
Section: Resultsmentioning
confidence: 99%
“…De nitely, effective and precise prognostic prediction in patients with malignancy is important for clinical decision-making and scienti c research. Previous studies had reported that factors such as age, sex, CEA, tumor size, T and N stage, metastatic sites, and treatment were signi cant predictors related to survival outcome of mCRC patients [10]. Intuitive and convenient prognostic tools are what clinicians need.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike it was clear that age was a prognostic factor in mCRC patients [21], whether sex, race, and tumor size had effects on the prognoses of patients with mCRC is still controversial. Some studies reported that white descent, male sex, larger primary tumor size predicts poorer survival [10,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation